Cytologic findings and differential diagnoses of primary thyroid MALT lymphoma with striking plasma cell differentiation and amyloid deposition. Issue 1 (2nd May 2013) - Nobuoka, Yuri; Hirokawa, Mitsuyoshi; Kuma, Seiji; Takagi, Nozomi; Higuchi, Miyoko; Masuoka, Hiroo; Miya, Akihiro; Kubota, Sumihisa; Miyauchi, Akira
<x xml:space="preserve">Abstract</x> We report two cases of thyroid mucosa‐associated lymphoid tissue (MALT) lymphoma with associated amyloid protein deposition. While other primary thyroid neoplasms sush as medullary carcinoma and plasmacytoma with associated amyloid protein are known to occur and have been previously described by fine‐needle aspiration cytology (FNAC), to our knowledge, the current cases are the first of thyroid MALT lymphoma with amyloid deposition to be detailed in the cytopathology literature. Case 1 was a 73‐year‐old female with chronic thyroiditis. FNAC suspected MALT lymphoma. The amyloid material was not noticed, nevertheless it existed. Case 2 was a 71‐year‐old female with a nodule of the thyroid. Malignant lymphoma and medullary carcinoma were suspected by FNAC. The possibility of medullary carcinoma was excluded by a measurement of serum calcitonin and carcinoembryonic antigen. After follow‐up for two years, the nodule was diagnosed as MALT lymphoma associated with plasma cell differentiation and amyloidosis by the fourth FNAC. When we encounter small round cell tumors associated with amyloid in thyroid FNAC, we should consider not only medullary carcinoma but also MALT lymphoma. Diagn. Cytopathol. 2014;42:73–77. © 2013 Wiley Periodicals, Inc.